2022
DOI: 10.1001/jamanetworkopen.2022.0562
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Prices Paid for Hemodialysis by Employer-Sponsored Insurance in the US From 2012 to 2019

Abstract: Author Contributions: Mr League had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Variation in prices paid for health care services is well-documented across geography and payer. [1][2][3][4][5][6] Studies find higher prices among private insurers than Medicare and Medicaid. 3,[6][7][8][9][10] These studies, however, are generally focused on adults, hospital prices, and comparisons between private insurers and Medicare, which rarely covers pediatric services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in prices paid for health care services is well-documented across geography and payer. [1][2][3][4][5][6] Studies find higher prices among private insurers than Medicare and Medicaid. 3,[6][7][8][9][10] These studies, however, are generally focused on adults, hospital prices, and comparisons between private insurers and Medicare, which rarely covers pediatric services.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in prices paid for health care services is well‐documented across geography and payer 1–6 . Studies find higher prices among private insurers than Medicare and Medicaid 3,6–10 .…”
Section: Introductionmentioning
confidence: 99%
“…15 The differences in spending between enrollees receiving dialysis with private insurance and those with Medicare are especially important given growing concerns about the market power of large dialysis organizations and recent policy proposals. For instance, League et al 8 reported that median prices per hemodialysis session for employer-sponsored plans were 6 times higher than Medicare prices, with the market power of large dialysis organizations one possible explanation for such high rates; the dialysis industry is highly concentrated, with DaVita Inc and Fresenius Medical Care combining to control a 72% share of the market. 16 Because many insurers have limited choice for providing dialysis benefits to their enrollees, large dialysis organizations may be able to command high prices.…”
Section: Discussionmentioning
confidence: 99%
“…To assess how health care spending changes after the start of dialysis, we compared monthly spending for patients before and after their first dialysis treatment with a multivariate regression model using Stata, version 17 (StataCorp LLC). Unlike previous studies that compared patients with kidney failure with different patients who did not receive dialysis care, 4 , 8 our longitudinal data allowed us to follow up patients receiving dialysis. In this way, we were able to control for unobserved, time-invariant differences in health across patients that may be associated with the onset of kidney failure, such as smoking, diet, or exercise habits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation